2022
DOI: 10.1007/s12070-022-03293-w
|View full text |Cite
|
Sign up to set email alerts
|

The Retrospective Pilot Study of the Prevalence of Olfactory Dysfunction or Loss of Smell, Loss of Taste and Oral Manifestations Among COVID-19 Positive Health Workers in Muscat, Oman

Abstract: A retrospective study evaluating the prevalence of loss of smell, loss of taste and oral manifestations was carried out by framing an online questionnaire and disseminated among the health care workers including medical and dental students, who were afflicted with COVID-19. The objective of this study was to find out the prevalence of the loss of smell, loss of taste (LOST) and oral manifestations and whether these (LOST & oral manifestations) can be the premonitory manifestations and also whether these can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… 37 , 39 , 40 , 42 , 43 , 45 , 48 , 52 , 53 , 60 , 63 , 66–68 Some of the cases were found as atrophy, 42 , 60 erosion, 42 , 48 , 60 pseudomembrane, 39 , 46 , 59 , 60 , 67 vesico-bullous, 39 , 43 blister, 39 , 67 nodule, 60 plaque, 59 , 60 depapilation, 39 , 67 , 68 macula, 40 , 42 , 45 , 46 , 60 , 67 petechiae, 43 ecchymosis, 43 fissure, 39 hematoma, 48 swelling and bleeding. 50 The patient was distributed equally between men and women aged 1–88 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 , 39 , 40 , 42 , 43 , 45 , 48 , 52 , 53 , 60 , 63 , 66–68 Some of the cases were found as atrophy, 42 , 60 erosion, 42 , 48 , 60 pseudomembrane, 39 , 46 , 59 , 60 , 67 vesico-bullous, 39 , 43 blister, 39 , 67 nodule, 60 plaque, 59 , 60 depapilation, 39 , 67 , 68 macula, 40 , 42 , 45 , 46 , 60 , 67 petechiae, 43 ecchymosis, 43 fissure, 39 hematoma, 48 swelling and bleeding. 50 The patient was distributed equally between men and women aged 1–88 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…[39][40][41][42][43][44] The prospective study reported oral lesions from all patients. 45 The retrospective reported 1.70-100% among COVID-19 patients, [46][47][48][49][50] and the cross-sectional reported 0.67-100% (Figure 2). [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] The Oral Lesions that Were Found in the Original Studies Most oral lesions reported in the original study were ulcers.…”
Section: The Original Studies Report On Oral Lesions In Covid-19 Pati...mentioning
confidence: 98%
“…The contagious disease rapidly became a pandemic on the world encompassing scale. It is known that this virus can cause severe respiratory failure and even death in infected patients (Al-Swiahb et al, 2021, Saraf et al, 2023, Song et al, 2021.…”
Section: Introductionmentioning
confidence: 99%